Development of Innovative Antifreeze Grout Mortar for Anchor Applications in Cold Regions. Issue 1 (January 2015) - Lin, Chuang; Liu, Jenny; Zhang, Xiong
Ground anchors and anchored systems have been successfully used as cost-effective soil supporting systems for highway safety considerations for decades. However, some unique challenges exist when these systems are used in Alaska and other cold regions. One challenge associated with anchor installation could be potential thawing of the warm permafrost as a result of grout mortar hydration; this thawing might undermine the capacity of the anchor. Therefore, this study aimed to develop an innovative antifreeze grout mortar for successful application of anchors in cold regions. A testing matrix of different combinations of chemical admixtures was developed, and workability, early-age strength, and freezing point of the mix water of mixes were evaluated to determine the optimum mix designs. Test results showed that the antifreeze grout mortar achieved three primary objectives: ( a ) it depressed the freezing point of the mix water available for the hydration process, ( b ) it accelerated the early-age strength gain at low temperature, and ( c ) it enhanced excellent flowability for grouting. The laboratory results were further validated through fieldwork in a test section located inside the Cold Region Research and Engineering Laboratory permafrost tunnel.